„Gdy lew zaryczy…” (Am 3,8). Obraz lwa w Księdze Amosa - Szmajdziński, Mariusz (Verbum Vitae, 2017)
The lion is known as the “king of beasts”. Its physical appearance, its strength, dignified movements and fierceness in killing have all left a deep impression upon the human mind. Not surprisingly, lions are mentioned in the Bible for their might (2Sam 1:23), boldness (2Sam 17:10), ferocity (Ps 7:2) and craftiness (Ps 10:9). Biblical leonine references occur in both literal and metaphorical usage. A “king of beasts”-type image is very often used to describe YHWH and His power, especially in the Prophets (Isa 5:29; 31:4; 38:13; Jer 25:38; 49:18-19; Hos 5:14; 13:7). Additionally, there are six mentions of the lion in the Book of Amos (Amos 1:2; 3:4,8,12; 5:19). There the prophet compares God to a lion, a word-picture which allows him to convey two core themes: First, the image serves to elucidate the relationship between God and the prophet – YHWH and His messenger. Amos achieves this through the metaphor of hearing the roar of the lion, an image of God’s voice, which in reality is heard by all people (Amos 1:2). Secondly, Amos heralds the coming punishment and its terror. God himself has spoken, and thus the prophet speaks (Amos 3:8). The key message of this second lion image in Amos is the inevitability of God’s punishment: in the same way that a lion devours its prey, YHWH will punish the crimes of Israel, and the Israelites will not be able to run from Him (Amos 3:4,12; 5:19).